Kelola Bandwidth Dengan Menerapkan Algoritma Per Connection Queue Pada Jaringan Komputer Rajawali Kupie - Nanda Pratama, Agung (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In this day and age generally in places of business using the internet wifi as a tourist attraction for endings, such as coffee shop business. However, it is not uncommon to find wifi facilities provided by coffee shops or coffee shops that cannot be used, usually this is caused by the many users of the wifi network, not to mention one of the users who performs downloading or streaming activities. This causes the allocation of available bandwidth to be captured entirely by users who carry out these activities, resulting in no allocation of the remaining bandwidth for other users. Therefore it is necessary to have a bandwidth processing to regulate bandwidth allocation for wifi network users. One solution to this problem is to manage bandwidth using a proxy routerboard, a proxy routerboard will manage bandwidth to the network using the algorithm per connection queue (PCQ), this algorithm will allocate bandwidth evenly according to the number of users on the wifi network, so the bandwidth distribution the network is carried out fairly and equally. With this bandwidth management it is expected to help the coffee shop management in overcoming problems in the wifi network